Systems Immunology Analyses Following Porcine Respiratory and Reproductive Syndrome Virus Infection and Vaccination - Bocard, Loïc Vivien; Kick, Andrew Robert; Hug, Corinne; Lischer, Heidi Erika Lisa; Käser, Tobias; Summerfield, Artur (Frontiers in Immunology, 2021)
This study was initiated to better understand the nature of innate immune responses and the relatively weak and delayed immune response against porcine reproductive and respiratory syndrome virus (PRRSV). Following modified live virus (MLV) vaccination or infection with two PRRSV-2 strains, we analyzed the transcriptome of peripheral blood mononuclear cells collected before, at three and seven days after vaccination or infection. We used blood transcriptional modules (BTM)-based gene set enrichment analyses. BTM related to innate immune processes were upregulated by PRRSV-2 strains but downregulated by MLV. In contrast, BTM related to adaptive immune responses, in particular T cells and cell cycle were downregulated by PRRSV-2 but upregulated by MLV. In addition, we found differences between the PRRSV strains. Only the more virulent strain induced a strong platelet activation, dendritic cell activation, interferon type I and plasma cell responses. We also calculated the correlations of BTM with the neutralizing antibody and the T-cell responses. Early down regulation (day 0-3) of dendritic cell and B-cell BTM correlated to both CD4 and CD8 T-cell responses. Furthermore, a late (day 3-7) upregulation of interferon type I modules strongly correlated to helper and regulatory T-cell responses, while inflammatory BTM upregulation correlated more to CD8 T-cell responses. BTM related to T cells had positive correlations at three days but negative associations at seven days post infection. Taken together, this work contributes to resolve the complexity of the innate and adaptive immune responses against PRRSV and indicates a fundamentally different immune response to the less immunogenic MLV compared to field strains which induced robust adaptive immune responses. The identified correlates of T-cell responses will facilitate a rational approach to improve the immunogenicity of MLV.